Seismic Responses of NPP Structures Considering the Effects of Lead Rubber Bearing - Nguyen, D. D.; Nguyen, C. N. (Engineering, Technology & Applied Science Research, 2020)
Abstract-This study investigates the effects of Lead Rubber Bearings (LRBs) on Floor Response Spectra (FRS) of Nuclear Power Plant (NPP) structures. Three main structures in the Advanced Power Reactor 1400 (APR1400) NPP including the reactor containment building, an internal structure, and an auxiliary building were numerically developed in SAP2000. The structures were modeled using beam stick elements, and lumped masses were assigned to beam element nodes. All equivalent section properties of beam elements were calculated based on the designed cross-sections of the structures. A series of 40 ground motions with response spectra scaled to match the NRC 1.60 spectrum were utilized in numerical time-history analyses. Finally, a thorough comparison of FRS was conducted at different elevations of the structures, considering both with and without LRB. Numerical results showed that the FRS of base-isolated structures at higher elevations was significantly reduced compared to non-isolated structures. However, at lower elevations, the FRS was higher for the base-isolated structures compared to the non-isolated ones. Additionally, at a low-frequency range, roughly smaller than 3 Hz, the FRS of base-isolated structures was always greater than that of the non-isolated ones.